Kolaborasi Pengembangan Wisata Alam Toga Raja di Desa Partungko Naginjang, Kabupaten Samosir: Collaborative Development of Toga Raja Ecotourism in Partungko Naginjang Village, Samosir Regency - Nur’ainiza Sitorus, Intan; Supsiloani, Supsiloani (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
The article aims to examine the collaboration among BUMDes (Village-Owned Enterprises), the village government, and the local community in developing the natural tourist destination Toga Raja and to describe the strategies employed in its development. The method used in this research is qualitative with a descriptive approach. Data were collected through observations and in-depth interviews. The findings of this study demonstrate that Toga Raja, as a pioneering ecotourism site, holds significant potential in the tourism sector, where collaboration among BUMDes, village government, and the local community is key to its successful development. The development strategies encompass the utilization of social media, cooperation with travel agencies, and the improvement of tourism facilities. The results are evident in the increased number of tourists and rising revenue over time. Toga Raja serves as a successful example of ecotourism development through strong collaboration between BUMDes, the village government, and the local community, employing effective strategies. Abstrak Artikel ini bertujuan untuk melihat kolaborasi yang dilakukan oleh BUMDes, pemerintah desa, dan masyarakat lokal dalam pengembangan wisata alam Toga Raja, dan menggambarkan strategi pengembangan yang dilakukan. Metode yang digunakan pada penelitian ini adalah penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data diperoleh dari observasi dan wawancara mendalam. Hasil kajian ini menunjukkan bahwa sebagai wisata alam rintisan, Toga Raja menawarkan potensi besar dalam bidang wisata di mana kolaborasi BUMDes, pemerintah desa, dan masyarakat lokal menjadi kunci sukses dalam pengembangan wisata ini. Strategi pengembangan meliputi pemanfaatan media sosial, kerjasama dengan agen travel, dan peningkatan fasilitas wisata. Hasilnya terlihat dengan peningkatan jumlah wisatawan dan pendapatan yang meningkat dari waktu ke waktu. Wisata Toga Raja adalah contoh sukses pengembangan wisata alam rintisan melalui kolaborasi yang kuat antara BUMDes, pemerintah desa, dan masyarakat lokal dengan strategi yang efektif.